PENYULUHAN AKUNTANSI PRAKTIS BAGI PELAKU UMKM DI KELURAHAN TEMBILAHAN HILIR KECAMATAN TEMBILAHAN - Novriani Susanti; Ria Febrina; Rosliana Rosliana (KARYA ABDI, 2022)
Tembilahan Hilir Village is one of the villages located in Batang Tuaka District, Indragiri Hilir Regency, Riau Province. In Tembilahan Hilir Village, there are various small and medium business fields. Unfortunately, not all UMKM actors understand accounting records in accordance with the applicable accounting system. Based on the results of observations, it is known that one of the factors behind the absence of accounting records is the educational background of UMKM actors. To assist UMKM actors in carrying out practical bookkeeping, counseling was carried out to UMKM actors in making practical accounting records. The purpose of this counseling is so that UMKM actors can apply practical accounting in their business. The method used is in the form of counseling to UMKM actors in Tembilahan Hilir Village. Based on the evaluation of the results of the counseling, most UMKM actors have understood bookkeeping using a practical accounting system.